Antioxidant Properties and Geroprotective Potential of Wheat Bran Extracts with Increased Content of Anthocyanins - Daria V. Mikhailova; Oksana G. Shevchenko; Denis A. Golubev; Elena Y. Platonova; Nadezhda V. Zemskaya; Olesya Yu. Shoeva; Elena I. Gordeeva; Sergey A. Patov; Mikhail V. Shaposhnikov; Elena K. Khlestkina; Alexey Moskalev (MDPI AG, 2023)
In recent years, there has been a focus on breeding wheat with high anthocyanin levels in order to improve food quality and human health. The objective of this study was to examine the antioxidant and geroprotective properties of wheat bran extracts using both in vitro and in vivo research methods. Two wheat lines were used: one with uncolored pericarp (anthocyanin-free) and another with colored pericarp (anthocyanin-containing). These lines differed in a specific region of chromosome 2A containing the Pp3/TaMyc1 gene, which regulates anthocyanin production. High-performance liquid chromatography-mass spectrometry revealed the presence of cyanidin glucoside and cyanidin arabinoside in the anthocyanin-containing wheat bran extract (+AWBE), while no anthocyanins were found in the anthocyanin-free wheat bran extract (−AWBE). The +AWBE showed higher radical scavenging activity (DPPH and ABTS assays) and membrane protective activity (AAPH oxidative hemolysis model) compared to the −AWBE. Both extracts extended the lifespan of female Drosophila, indicating geroprotective properties. This study demonstrates that wheat bran extracts with high anthocyanin levels have antioxidant and geroprotective effects. However, other secondary metabolites in wheat bran can also contribute to its antioxidant and geroprotective potential.